2020
DOI: 10.1111/jai.14017
|View full text |Cite
|
Sign up to set email alerts
|

The length‐weight relationship of four fish species captured in the Ibicuí River, southern Brazil

Abstract: Length‐Weight relationship (LWRs) were estimated for four fish species occurring in the Ibicuí River drainage basin, southern Brazil. Samples were captured monthly during the spring and summer seasons (October 2018 to March 2019). The fish were caught with gillnets of different meshes (15, 20, 25, 30, 40 mm between adjacent nodes) and a trawl net (5 mm mesh between adjacent nodes) Eighteen excursions were realized in three sites, with a length of approximately 100 km, in third‐order flux, all distributed in su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…This pattern is as reported by Amarasinghe ( 2002) with a value of b: 2,699 in the Shallow Irrigation Reservoir in Sri Lanka. The difference in growth patterns is caused by several factors, including differences in age, gonad maturity, sex, geographical location, and environmental conditions (fishing activity), stomach fullness, disease, and parasite pressure (Nobile et al 2015;Froese and Pauly 2019;Pachla et al 2020;Yonvitner et al 2020). The asymptotic length of Nile Tilapia found in Siombak Lake reaches 36.04 cm.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern is as reported by Amarasinghe ( 2002) with a value of b: 2,699 in the Shallow Irrigation Reservoir in Sri Lanka. The difference in growth patterns is caused by several factors, including differences in age, gonad maturity, sex, geographical location, and environmental conditions (fishing activity), stomach fullness, disease, and parasite pressure (Nobile et al 2015;Froese and Pauly 2019;Pachla et al 2020;Yonvitner et al 2020). The asymptotic length of Nile Tilapia found in Siombak Lake reaches 36.04 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, other studies found to be negative allometric as reported in the Infiernillo Reservoir, Mexico [42], in the Rosetta branch of the Nile River, Egypt [43], in the Aguamilpa Reservoir, Mexico [44], and the Nozha Hydrodrome, Egypt [45]. The difference in growth patterns is affected by several factors, including differences in geographical location, season, sex, stage of fish maturity, food availability, stomach fullness, health, stress and sampling methodology [21,46,34,47].…”
Section: Discussionmentioning
confidence: 99%
“…However, some authors found that the species' growth demonstrated an isometric growth pattern [2,43,12]. The growth pattern of the species can be affected by several influences, including the environmental conditions between different geographical locations, seasons, sex, stage of maturity, stomach fullness, diseases, and sampling methodology [26,[44][45][46]. "Growth parameters and mortality rates of fish are crucial inputs for stock assessments.…”
Section: Conclusion and Discussionmentioning
confidence: 99%